2017
DOI: 10.1155/2017/7584691
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol Prevents ROS‐Induced Apoptosis in High Glucose‐Treated Retinal Capillary Endothelial Cells via the Activation of AMPK/Sirt1/PGC‐1α Pathway

Abstract: Resveratrol (RSV) is used as a protective therapy against diabetic retinopathy. However, the mechanism(s) underlying this protective effect has not been fully elucidated. Bovine retinal capillary endothelial cells (BRECs), an in vitro model, were used to investigate the mechanism of RSV. Our results showed that high glucose induced significant cellular apoptosis in BRECs, which was accompanied by increased intracellular levels of reactive oxygen species (ROS) and cleaved caspase-3. The glucose-induced apoptosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
70
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(75 citation statements)
references
References 42 publications
5
70
0
Order By: Relevance
“…To date, mitochondrial production of ROS in response to HG may also be a key initiating step in the pathogenesis of DR (29). Our results showed that HG stimulation caused significant increase in the production of ROS in HRECs and the involvement of transcription levels of the oxidative stress associated genes was confirmed.…”
Section: Discussionsupporting
confidence: 67%
“…To date, mitochondrial production of ROS in response to HG may also be a key initiating step in the pathogenesis of DR (29). Our results showed that HG stimulation caused significant increase in the production of ROS in HRECs and the involvement of transcription levels of the oxidative stress associated genes was confirmed.…”
Section: Discussionsupporting
confidence: 67%
“…Other previous investigations have similarly demonstrated that resveratrol lowers ROS levels and increases SOD activity in vitro . Also in animal models of DR, resveratrol has been shown to decrease iPF 2 α levels, increase SOD activity and reduce glutathione levels .…”
Section: Resultsmentioning
confidence: 54%
“…Resveratrol (RSV) is a pleiotropic phytochemical found in peanuts and grapes that has been indicated to provide a wide range of health benefits, such as reducing oxidative, inflammatory, and apoptotic signals [122]-protecting against neurological decline [123], improving cardiovascular health [124], ameliorating diabetes [125], and preventing cancer [126]. The anticancer properties of RSV act through diverse molecular mechanisms that have been investigated in a plethora of cellular and animal models [127,128]…”
Section: Resveratrolmentioning
confidence: 99%